2005
DOI: 10.1080/15572536.2006.11832837
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic hyphomycetes as endophytes of riparian plant roots

Abstract: Eighteen species of aquatic hyphomycetes were recorded as root endophytes in roots of living plants including grasses and pteridophytes from wet fields near ravine areas. Alatospora acuminata, A. pulchella, Acaulopage tetraceros, Anguillospora crassa, Campylospora chaetocladia, Lemonniera cornuta, L. pseudofloscula, L. terrestris, Pestalotiopsis submersus and Tetrachaetum elegans were found for the first time as root endophytes. A. longissima, Campylospora purvula, Clavariopsis aquatica, Cylindrocarpon aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…It was earlier reported from freshwater streams of Kumaun Himalaya (Tiwari & Sati 1991) and as root endophyte from Kumaun Himalaya (Sati & Belwal 2005). This isolate was found very much similar to the species described by Ranzoni (1953) as well as Descals et al (1977).…”
Section: Lemonniera Cornuta Ranzonisupporting
confidence: 64%
See 3 more Smart Citations
“…It was earlier reported from freshwater streams of Kumaun Himalaya (Tiwari & Sati 1991) and as root endophyte from Kumaun Himalaya (Sati & Belwal 2005). This isolate was found very much similar to the species described by Ranzoni (1953) as well as Descals et al (1977).…”
Section: Lemonniera Cornuta Ranzonisupporting
confidence: 64%
“…Earlier it was reported from freshwater streams ofJeolikoteandJageshwarinKumaun Himalaya (Sati et al 2002) and also as root endophyte of Lyoniaovalifolia (Sati & Belwal 2005). The Kumaun Himalayan isolate L. pseudofloscula hasshorter conidial arms than the species described by Descals et al (1977).The number of septa in Kumaun Himalayan isolate is 2−5 per arm while Descals et al (1977) reported 7 septa in each arm.…”
Section: Lemonniera Pseudofloscula Dykomentioning
confidence: 83%
See 2 more Smart Citations
“…Endophytic fungi are reported from plants that grow in various environments including tropic (Mohali et al 2005), temperate (Ganley et 27 al. 2004), xerophytic (Suryanarayanan et al 2005) coastal mangroves (Kumaresan & Suryanarayanan 2001, Okane et al 1998) and aquatic environment (Sati & Belwal 2005). Environment plays an important role on endophyte biodiversity, while the species diversity is dependent upon the nature of the host plant and their ecological location.…”
Section: Introductionmentioning
confidence: 99%